Pengenalan dan Edukasi Literasi Keuangan Sederhana melalui Gerakan Menabung Sejak Dini pada Anak SD - Anisah Anisah; Fauzani Fauzani; Sirajudin Al Aksari; Jexki Jexki; Elma Prizila; Nurmala Artika (LPPM UNIVERSITAS DIAN NUSWANTORO, 2026)
This Community Service Activity (PKM) aims to introduce and improve basic financial literacy among primary school pupils through an early savings initiative in Panca Karya Village. Financial literacy is a crucial aspect in fostering wise economic behaviour, particularly when instilled from an early age. The challenges faced include students’ limited understanding of financial management and the lack ofestablished consistent saving habits. The activity was implemented through three stages: preparation,implementation, and evaluation. During the implementation stage, pupils were provided with interactive education on basic financial concepts such as the function of money, the difference between needs and wants, and the importance of saving, followed by hands-on saving practice. The results of the activity showed an improvement in pupils’ understanding of basic financial literacy, evidenced by their ability to explain the concept of saving and its benefits. Furthermore, there has been a shift in pupils’ attitudes towards the use of their pocket money, leading them to spend more wisely, as well as a growing motivation to save regularly. The active participation of pupils and the support of the school have been key factors in the success of this programme. This initiative not only enhances cognitive development but also fosters positive financial attitudes and behaviours among pupils. Consequently, the financial literacy education programme, through the early savings initiative, has a significant impact on building a disciplined character and a sense of financial responsibility in children. This initiative also has the potential to be developed into a sustainable programme within the school environment to strengthen a culture of financial literacy from an early age.